Effect of Quercetin Supplementation in Extender on Sperm Kinematics, Extracellular Enzymes Release, and Oxidative Stress of Egyptian Buffalo Bulls Frozen–Thawed Semen - El-Khawagah, Ahmed R. M.; Kandiel, Mohamed M. M.; Samir, Haney (Frontiers in Veterinary Science, 2020)
Buffalo spermatozoa are more sensitive for cryopreservation compared to other species. This study aimed to evaluate the consequences of quercetin against cryodamage of buffalo frozen-thawed spermatozoa characteristics. Semen of Egyptian bulls (n=4) was extended in OptiXcell extender incorporated with quercetin at 0 (control), 2.5, 5.0, 10.0, 20.0, 40.0 and 80.0µM before cryopreservation. Frozen-thawed semen was evaluated for sperm motility by CASA, viability, morphology, membrane, and acrosome integrities. The kinematics parameters including Average path velocity (VAP; μm/s), Straight linear velocity (VSL; μm/s), Curvilinear velocity (VCL; μm/s), Amplitude of lateral head displacement, (ALH; μm), Beat cross frequency (BCF; Hz), Linearity (LIN, [VSL/VCL] × 100), and Straightness (STR, [VSL/VAP] × 100) were assessed. The sperm-free extender was evaluated for aspartate aminotransferase (AST), Alanine aminotransferase (ALT), and H2O2. Homogenized sperm cells were evaluated for oxidative stress biomarkers (Superoxide dismutase (SOD), Catalase (CAT), Glutathione peroxidase (GPX)), and lipid peroxidation (Malondialdehyde (MDA)). The highest values of total motility, progressive motility, viability, intact acrosome, membrane integrity substantially improved with 10 µM of quercetin. STR (%) was substantially low (P<0.01), and VCL (µm/s) and ALH (µm) were markedly high (P<0.05) in 10 µM of quercetin. The outflow of ALT enzyme to extracellular fluid was lower with 10 µM of quercetin (P<0.001), and higher at 2.5 µM of quercetin. The spermatozoa leaked AST was markedly lower at 5.0, 10 (P<0.001), and 20 µM (P<0.05) of quercetin. The activity of antioxidant enzymes was eminently low at all quercetin concentrations, and this was accompanied by the decrease of H2O2 in the media. SOD activity at 10-80 µM, CAT at 5.0-40 µM, and GPX at 2.5-80.0 µM of quercetin in spermatozoa were substantially low. MDA level significantly (P<0.001) decreased at all quercetin concentrations. In conclusion, the incorporation of quercetin at the level of 10 µM is promising in improving buffalo semen characteristics and lower the freezing-thawing oxidative stress.